Pelaksanaan Community Based Edutourism di Kawasan Bedugul dan Pancasari (Jurnal Ilmiah Pariwisata, 2014)
This study aims to : ( 1 ) obtain a practical model of Community Based Edutourism (CBE) relating to the planning , implementation , and management of CBE to the creation of sustainable tourism , and ( 2 ) determine the effectiveness of CBE visible impact on the local economy . The method used is a design research that consist of preliminary research, prototyping, and assessment. Data were collected through observation , questionnaires , and interviews. Then the data were analyzed descriptively . The results of this study are : ( 1 ) the model CBE using three strategies, namely , the development of CBE products in accordance with the existing potential ; increase the ability of communities in the management or services in accordance with existing resources , and develop tour packages and promotions are a practical quality; and ( 2 ) the development of CBE tends to be effective seen the growth of the local economy . The development of the CBE gets a very positive response both from the village , tourism industry , society , and the education providers . In accordance with these human resource development needs to be done , and promotion should be improved by involving travel-travel agent . In addition , the local government should soon to develop infrastructures to better support and interest in the CBE .